AN INVESTIGATION OF UPPER MANTLE HETEROGENEITY BENEATH THE ARCHAEAN AND PROTEROZOIC CRUST OF WESTERN CANADA FROM LITHOPROBE CONTROLLED-SOURCE SEISMIC EXPERIMENTS - Gorman A.R.; Németh B.; Clowes R.M.; Hajnal Z. (My University, 2006)
Observations of upper mantle reflectivity at numerous locations around the world have been linked to the presence of a heterogeneous distribution of rock types within a broad layer of the upper mantle. This phenomenon is observed in wide-angle reflection data from Lithoprobe's Alberta Basement Transect [the SAREX and Deep Probe experiments of 1995] and Trans-Hudson Orogen Transect [the THoRE experiment of 1993]. SAREX and Deep Probe image the Archaean lithosphere of the Hearne and Wyoming Provinces, whereas THoRE images the Archaean and Proterozoic lithosphere of the Trans-Hudson Orogen and neighbouring areas. Finite-difference synthetic seismograms are used to constrain the position and physical properties of the reflective layer. SAREX/Deep Probe modelling uses a 2-D visco-elastic finite-difference routine; THoRE modelling uses a pseudospectral algorithm. In both cases, the upper mantle is parameterized in terms of two media. One medium is the background matrix; the other is statistically distributed within the first as a series of elliptical bodies. Such a scheme is suitable for modelling: (1) variations in lithology (e.g., a peridotite matrix with eclogite lenses) or (2) variations in rheology (e.g., lenses of increased strain within a less strained background). The synthetic seismograms show that the properties of heterogeneities in the upper mantle do not change significantly between the two Lithoprobe transects. Beneath the Trans-Hudson Orogen in Saskatchewan, the layer is best modelled to lie at depths between 80 and 150 km. Based on observations from perpendicular profiles, anisotropy of the heterogeneities is inferred. Beneath the Precambrian domains of Alberta, 400 km to the west, upper mantle heterogeneities are modelled to occur between depths of 90 and 140 km. In both cases the heterogeneous bodies within the model have cross-sectional lengths of tens of kilometers, vertical thicknesses less than 1 km, and velocity contrasts from the background of -0.3 to -0.4 km/s. Based on consistency with complementary data and other results, the heterogeneous layer is inferred to be part of the continental lithosphere and may have formed through lateral flow or deformation within the upper mantle. © 2006 Elsevier B.V. All rights reserved.
Keywords: CONTROLLED-SOURCE SEISMOLOGY; FINITE-DIFFERENCE MODELLING; UPPER MANTLE HETEROGENEITY; WESTERN CANADA; Proterozoic; Cambrian; Precambrian::Proterozoic; Докембрий::Протерозой; Paleozoic::Cambrian; Палеозой::Кембрийская